2017
DOI: 10.1515/boku-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis of winter wheat cultivars as affected by nitrogen fertilization / Wachstumsanalyse von Winterweizensorten in Abhängigkeit von Stickstoffdüngung

Abstract: SummaryGrowth analysis helps explain the differences in yield and growth potential between cultivars in response to management practices and environmental conditions. The aim of the research was: (i) to investigate the effect of nitrogen fertilization on the growth and growth parameters of different wheat (Triticum aestivum L.) cultivars and (ii) to study the relationship between yield and growth parameters at the individual plant and plant stand level. In the two-factorial, split-plot experiment, the main plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
2
1
0
2
Order By: Relevance
“…The indices AGR, ALGR, and CGR presented a positive correlation with seed yield (r=0.7875, p<0.001; r=0.6320, p<0.001; and r=0.7875, p=0.002, respectively). These results are in accordance with previous studies presenting the significant relationship between growth rate parameters and yield in other crops, such as wheat (Sugár et al, 2017), maize (Bullock et al, 1993), oilseed rape (Hunková et al, 2011) and Nigella sativa (Roussis et al, 2019). Seed yield was only affected by fertilization and the highest value was found in plants fertilized with the highest rate of inorganic nitrogen fertilizer (200 kg N ha -1 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The indices AGR, ALGR, and CGR presented a positive correlation with seed yield (r=0.7875, p<0.001; r=0.6320, p<0.001; and r=0.7875, p=0.002, respectively). These results are in accordance with previous studies presenting the significant relationship between growth rate parameters and yield in other crops, such as wheat (Sugár et al, 2017), maize (Bullock et al, 1993), oilseed rape (Hunková et al, 2011) and Nigella sativa (Roussis et al, 2019). Seed yield was only affected by fertilization and the highest value was found in plants fertilized with the highest rate of inorganic nitrogen fertilizer (200 kg N ha -1 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the maximum LAI and LAD values were recorded in in plants treated with the highest rate of inorganic nitrogen fertilizer (200 kg N ha -1 ) at the beginning of anthesis (75 DAS) and throughout the period between flowering stage and the first days of grain formation (75-100 DAS), respectively. This is in accordance with previous studies demonstrated that increase in aboveground dry matter due to the application of higher rates of nitrogen related with higher LAI and LAD values (Bullock et al, 1993;Sugár et al, 2017). Seed yield had a positive and close association with LAI and LAD (r=0.7479, p<0.001 and r=0.7183, p<0.001, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(r = 0,7416, p < 0,0001, r = 0,7741, p < 0,0001, r = 0,5581, p < 0,0001και r = 0,3207, p = 0,0060, αντίστοιχα; Σχήµα 4.4). Αυτά τα αποτελέσµατα ευθυγραµµίζονται µε άλλες µελέτες που παρουσιάζουν σηµαντική συσχέτιση µεταξύ του ρυθµού ανάπτυξης και της απόδοσης σε διάφορες καλλιέργειες, όπως το σιτάρι (Sugár et al, 2017), ο αραβόσιτος (Bullock et al, 1993), τα ζαχαρότευτλα (Hoffmann and Kluge-Severin, 2011) και η ελαιοκράµβη (Hunková et al, 2011). Επίσης, οι δείκτες που προσδιορίζουν ρυθµούς ανάπτυξης (AGR, ALGR, RGR, CGR), επηρεάστηκαν θετικά από τη λίπανση και τα αποτελέσµατα ήταν σύµφωνα µε την αύξηση του ξηρού βάρους των φύλλων και της υπέργειας βιοµάζας καθώς και µε την απόδοση της καλλιέργειας σε σπόρο.…”
Section: φυτικές παράµετροιunclassified
“…Σύµφωνα µε αρκετούς ερευνητές (Pepó and Novák, 2016;Tagliapietra et al, 2018), υπάρχει µια στενή θετική σχέση µεταξύ του δείκτη φυλλικής επιφάνειας (LAI) και της απόδοσης της καλλιέργειας σε σπόρο. Θετικές συσχετίσεις µεταξύ της χρονικής µεταβολής φυλλικής επιφάνειας (LAD) και της απόδοσης της καλλιέργειας σε σπόρο έχουν επίσης παρατηρηθεί και σε άλλες καλλιέργειες, όπως το σιτάρι (Sugár et al, 2017) και η ελαιοκράµβη (Hunková et al, 2011). Όσον αφορά τη λίπανση, υπήρξε σηµαντική επίδραση των διαφορετικών λιπάνσεων στην απόδοση της καλλιέργειας µελάνθιου σε σπόρο.…”
Section: φυτικές παράµετροιunclassified